(untitled) (Communication & Society, 2021)
Smartphone use influences teenagers’ behaviors and lifestyles, not always in a positive way. Abuse and dependence on the use of this device is what has led to the study of nomophobia. The objective of this research is to measure the level of nomophobia in adolescents, and to study their digital consumption habits. The study seeks to analyze the relationships between risk of nomophobia, digital behavior, age and smartphone use. A structured questionnaire has been applied to a sample of 850 students aged 12 to 16. The data has been analyzed with SPSS and SPAD. Multivariate statistical characterization, one of the most recent data mining techniques, has been used to study differences in teenagers’ behaviors according to their risk of nomophobia, and to find related explanatory variables. Teenagers’ nomophobia risk ranges from mild to moderate, showing a relation with age, academic performance and intensity of use of mobile social networking apps. The risk of nomophobia responds to differences in students’ digital, social, relational and educational behaviors, and exhibits differences according to academic performance, age, gender, motivation and self-perception.